Kajian Numerik Penerapan Heat Pump sebagai Sarana Penyimpanan Energi Skala Jala-Jala dari Pembangkit Energi Terbarukan - Refi Afrilia; Eko Julianto; Burniadi Moballa (Politeknik Perkapalan Negeri Surabaya, 2023)
Utilization of New Renewable Energy (EBT) today must be carried out because of its abundantpotential. One of the uses is to use energy storage with a heat pump system sourced from EBT. To supportthis, it is necessary to use a heat exchanger in an energy storage system which is expected to make theheating or cooling system faster with the right refrigerant. Therefore, a study was carried out using theapplication of a heat pump system with the addition of a heat exchanger as a place to store energyoriginating from Renewable Energy. The method used is process simulation using DWSIM. The refrigerantused is R-600a, R-407C. R-410a, R-22, and ammonia. Ammonia was chosen because it produces aCoefficient of Performance of 3.012 with a condenser outlet temperature of 102.854°C. The storagemedium used is silica sand.